The SmartAG partner: CCAFS East Africa Bi-Annual Newsletter, July - December 2018 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
We are pleased to share with you our SmartAg Partner bi-annual newsletter, highlighting policy engagement, ongoing research, field updates and activities with partners from the second half of 2018.